The Effect of Competency, Discipline and Compensation on Employee Performance: The Case of Population and Civil Registration Office of Palembang City - Isa, Muhammad; Rahayu, Sri; Moelyati, Trisniarty Adjeng (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study aims to determine 1) The Effect of Competence, Discipline, and Compensation on the Performance of Digital Population Identity (IKD) Service Officers at the Palembang City Population and Civil Registration Service Office. 2) The Effect of Competence on the Performance of Digital Population Identity Service Officers (IKD) of the Population and Civil Registration Office of Palembang City. 3) The Effect of Discipline on the Performance of Digital Population Identity Service Officers (IKD) of the Population and Civil Registration Office of Palembang City. 4) The Effect of Compensation on the Performance of Digital Population Identity Service Officers (IKD) of the Population and Civil Registration Office of Palembang City. This type of research is Associative. The variables used by researchers include Competence, Discipline, Compensation, and Performance. The population of this study consisted of all employees of the Population and Civil Registration Office in Palembang City, and the sample size in the study was 101 employees. The sampling technique used was Proportionate Stratified Random Sampling. The data used in this study were primary data with a questionnaire data collection method. The data analysis technique used was multiple linear regression, as implemented in the SPSS Program Application. The results of this study indicate that: 1) Competence, Discipline, and Compensation significantly influence the performance of Digital Population Identity (IKD) Service Officers at the Palembang City Population and Civil Registration Office. 2) Competence significantly influences the performance of Digital Population Identity (IKD) Service Officers at the Palembang City Population and Civil Registration Office. 3) Discipline significantly influences the performance of Digital Population Identity (IKD) Service Officers at the Palembang City Population and Civil Registration Office. 4) Compensation significantly influences the performance of Digital Population Identity (IKD) Service Officers at the Palembang City Population and Civil Registration Office